المحاسبة الإبداعية في الشركات الجزائرية - حسياني, عبد الحميد (جامعة الوادي - University of Eloued, 2015)
للمحاسبة عدة تعاريف فبعكس الرياضيات فالمحاسبة تدخل ضمن مجموعة من القواعد الغير صارمة والغير واضحة المعالم كما ينبغي، فالمحاسبة هي الفضاء الذي يستطيع فيه المسئولين والمديرين في الشركات العمل ببعض من الحرية ما يسمح بحدوث ما يسمى التلاعب في نتائج الشركة وذلك لرفع قيمة الشركة في السوق. لهذا كان الاتجاه الذي اتخذته الجزائر نحو النظام المحاسبي المالي المستمد من المعايير المحاسبية الدولية نقطة مهمة في هذا المجال باعتبار أن النظام المحاسبي المالي يعطي حرية للمسيرين اكبر من المخطط المحاسبي القديم فرصة لإلقاء الضوء على مفهوم المحاسبة الإبداعية في ظل النظام المحاسبي الجديد. Accounting has several definitions contrary to mathematics, accounting within a set of rules are not strict and not well defined as it should; the accounting, is the space of information about an enterprise and the transmission of that information from those who have it to those who need it, and managers in companies working with some of the freedom that allows to manipulate the results of the company to raise the company's market value. This was the trend taken by Algeria towards financial accounting system derived from the international accounting standards, is an important point in this area, considering that the financial accounting system gives managers greater freedom from the old accounting scheme an opportunity to shed light on the concept of creative accounting under the new accounting system.
مقال
Keywords: النظام المحاسبي المالي، القوائم المالية، المحاسبة الإبداعية، المراجعة، الحوكمة.; financial accounting system, financial statements, creative accounting, audit, corporate governance